Physical and mechanical properties of sterilized oil palm fruits at different component - Wondi, Mohd Hafizz; Shamsudin, Rosnah; Yunus, Robiah; Baharudin, Mohd Shafril; Arnan, Muhammad Zaidy; Abdu Rahman, Amirul Faizi (Shin-Norinsha, 2021)
The aim of current work is to investigate the physical and mechanical properties of sterilized oil palm fruit (Dura variety) and its component (kernel and nut) prior to mesocarp and nut separator machine development. The fresh fruit bunch (FFB) samples were sterilized at 100 °C for 140 minutes at 1 atm by using a continuous sterilizer and oil palm fruits were stripped from the bunch manually. Physical properties included the length, width, thickness, mean diameter (geometric and arithmetic), gravimetric properties, and frictional properties were measured. Standard methods were applied in determining the physical properties of the sample. The mechanical properties evaluated were rupture force, deformation at rupture point, hardness and energy. The mechanical properties parameters were determined using Universal Testing Machine. The overall findings show that the average length, width, and thickness of the palm fruitlet were the highest compared to nut and kernel which were 37.28, 25.06 and 21.64 mm, respectively. The shape of the kernel is closer to a sphere compared to the whole fruit and nut as the sphericity value obtained was 79.25. True densities of whole fruits, nuts and kernels were 1079.77, 1140.86 and 1284.76 kg/m3, bulk densities were 767.37, 536.77 and 515.72 kg/m3 whereas the porosity were 20.27, 51.29 and 52.39, respectively. Rupture force, deformation and hardness of sterilized whole fruit, nut and kernel were 878.23, 712.51 and 339.07 N, and 4.86, 3.70 and 2.40 mm, 180.71, 192.57 and 141.27 N.mm, respectively. Overall, the collected data are beneficial for the design of machinery related to oil palm fruit processing such as mesocarp and nut separator machine.